Rich food for poor people: Genetically improved tilapia in the Philippines - Yosef, Sivan (International Food Policy Research Institute, 2009)
The Genetic Improvement of Farmed Tilapia (GIFT) project, which operated from 1988–97, served as a launching point for tilapia improvement efforts in Asia, as well as tropical finfish genetic improvements globally. Based on the selective breeding of Nile tilapia, the GIFT project succeeded in producing tilapia with faster growth rates, higher survival rates, and a shorter harvest time, thus increasing fish yields dramatically. These attributes, along with its stable, low price, have made tilapia an extremely popular food source in Asia, especially among poor consumers. The resounding success of tilapia production was buoyed by strong institutional support from national and international research institutions, regional networks, governments, donors, and small-scale, private actors. Most importantly, a strong initial mandate to apply the GIFT project design to improve aquaculture in general makes GIFT an exciting and replicable benchmark for future food security efforts.